2021
DOI: 10.1177/1468796821989819
|View full text |Cite
|
Sign up to set email alerts
|

Segmenting anti-Muslim sentiment in Australia: Insights for the diverse project of countering Islamophobia

Abstract: Islamophobia is a global issue. Our nationwide survey of Australians, undertaken in 2015 and 2016, reveals the extent of this national calamity in Australia. But Islamophobia is not universal in its manifestation. Latent Class Analysis was used to develop a typology of Islamophobia in Australia. The results place Australians in four classes based on their perception of Islam: Islamophobes (13% of the population); those who are unsure about diversity and have some concerns about Muslims (24%), those with progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 58 publications
0
10
0
1
Order By: Relevance
“…In our dominant profiles, those with university education are only angry if they are older than 50, an indication of the clear interdependence of these variables when examining views on Islam and Muslims. The predominance of older and non-university-educated Australians in the causal recipes for anger towards both Islam and Muslims, along with the interdependence of those variables within Australian society and evidence of a non-causal relationship between education and prejudice, suggests that age is the factor of most interest: as noted by Dunn et al (2021), a positive sign for the future of out-group acceptance. However, regardless of whether increasing the level of education reduces someone's likelihood of being angry or unfavourable towards out-groups, or whether that out-group attitude is somehow set among other factors that instead predict level of education, the evidence remains that the causal recipes for above-average anger with Muslims among Australians in our study all include education levels below high school or at technical institutions, which may be of use to policy-makers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our dominant profiles, those with university education are only angry if they are older than 50, an indication of the clear interdependence of these variables when examining views on Islam and Muslims. The predominance of older and non-university-educated Australians in the causal recipes for anger towards both Islam and Muslims, along with the interdependence of those variables within Australian society and evidence of a non-causal relationship between education and prejudice, suggests that age is the factor of most interest: as noted by Dunn et al (2021), a positive sign for the future of out-group acceptance. However, regardless of whether increasing the level of education reduces someone's likelihood of being angry or unfavourable towards out-groups, or whether that out-group attitude is somehow set among other factors that instead predict level of education, the evidence remains that the causal recipes for above-average anger with Muslims among Australians in our study all include education levels below high school or at technical institutions, which may be of use to policy-makers.…”
Section: Discussionmentioning
confidence: 99%
“…Belief in the self's membership of a strong in-group, as experienced through exposure to confirmatory newspaper headlines, is associated with the emotion of anger towards an out-group, and in turn the tendency to want to act offensively towards the out-group (Mackie et al, 2000). Dunn et al (2021) examine what Islamophobia looks like in Australia by developing a typology of Islamophobia among Australians using latent class analysis (LCA). Through two surveys of Australians in 2015 and 2016 these researchers identify four groups of Australians with varying perceptions of Islam based on their 'fears, dispositions and likely actions ' (2021, p. 556).…”
Section: Australiamentioning
confidence: 99%
See 1 more Smart Citation
“…Using four different national samples, a study from the Netherlands found that between 13% and 22% of majority members have negative attitudes towards Turks and Moroccans (ethnic groups typically associated with Islam) and simultaneously object to Muslim rights to express their faith, wear a headscarf, celebrate Islamic holidays, build mosques and establish Islamic schools . A recent study from Australia showed that 13% of Australians display consistent anti-Muslim sentiments: they are negative towards Muslims as a group of people, would not like their relative to marry a Muslim, and would not support the building of a place of worship (Dunn et al, 2021).…”
Section: Prejudice-based Rejection Of Muslim Practicesmentioning
confidence: 99%
“…Met behulp van vier verschillende nationale steekproeven bleek uit een onderzoek uit Nederland dat meerderheidsleden een negatieve houding hebben ten opzichte van Turken en Marokkanen (etnische groepen die typisch worden geassocieerd met de islam) en tegelijkertijd bezwaar maken tegen moslimrechten, zoals het recht om hun geloof te uiten . Een recente studie uit Australië toonde aan dat sommige Australiërs consistent anti-moslim sentimenten vertonen door negatief te zijn tegenover moslims als een groep mensen, door niet te willen dat hun familielid met een moslim trouwt en door de bouw van een gebedshuis niet te steunen (Dunn et al, 2021 ). In lijn hiermee vond een onderzoek in Zwitserland dat sommige Zwitsers het sterk eens zijn met elk argument tegen de moslimpraktijk van het dragen van een gezichtssluier en een negatieve anti-moslim en antiislamhouding hebben (Eugster, 2021).…”
Section: Op Vooroordelen En Op Principes Gebaseerde Afwijzing Van Mos...unclassified